Točkovno talilno varjenje z oplaščeno elektrodo z ugreznjenim oblokom - Tušek, Janez (Materiali in tehnologije, 2002)
This paper reports on spot-plunged arc welding with a covered electrode. It is introduced by a description of the Marangoni effect as a basic phenomenon for a description of weld-pool movement. The type and intensity of the weld-pool movement play a decisive role in achieving a satisfactory penetration depth. And this is achieved by spot-plunged arc welding. The majority of the paper is focused on a description of the spot-plunged arc-welding process with a covered electrode. A diagram shows the movement of the cold and hot electrode ends during welding. The welding process is described in seven phases by the covered-electrode movement. A table gives an approximate chemical composition of the coating of the covered electrode. Several macro specimens of spot welds in lap joints made on plates of different thicknesses are shown. Chemical compositions of the weld metal and the parent metal are given. As an indicator of the economy of spot-plunged arc welding, a melting rate is indicated. Several figures show the shape and volume of the parent metal and the filler material melted.
Keywords: točkovno varjenje; obločno varjenje; talina; zvari; Maragonijev efekt